2011
DOI: 10.1002/icd.738
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Control of Attention and Selective Encoding for Preschoolers' Learning

Abstract: Selectivity in encoding, aspects of attentional control and their contribution to learning performance were explored in a sample of preschoolers. While the children are performing a learning task, their encoding of relevant and attention towards irrelevant information was recorded through an eye-tracking device. Recognition of target items was used as measure of learning outcome, and individual differences in resistance to interference and inhibition of attention to task-irrelevant stimuli (i.e. distractibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(52 reference statements)
1
19
2
Order By: Relevance
“…The present study also found similar results to those of Roderer, Krebs, Schmid, and Roebers (2012) with regard to distractibility and engagement. In their study of selective encoding for learning, they found that preschoolers were able to increase attention towards relevant stimuli of the present study, preschoolers seem able to increase attention towards relevant stimuli also in TA-based learning environments which are more visually complex and narratively elaborated.…”
Section: Discussionsupporting
confidence: 90%
“…The present study also found similar results to those of Roderer, Krebs, Schmid, and Roebers (2012) with regard to distractibility and engagement. In their study of selective encoding for learning, they found that preschoolers were able to increase attention towards relevant stimuli of the present study, preschoolers seem able to increase attention towards relevant stimuli also in TA-based learning environments which are more visually complex and narratively elaborated.…”
Section: Discussionsupporting
confidence: 90%
“…9,1722 Furthermore, evidence of the effectiveness of targeted interventions to improve EF skills is mounting. 2326 Hence, it is important to identify conditions associated with EF risk to promote early assessment and targeted intervention.…”
mentioning
confidence: 99%
“…proposed three functions of memory strategies, including 1. offering organizational structure to assist in learning and acquire message, 2. systematically storing learning materials into the memory structure to help remain learning materials in the memory without being forgotten, and 3. providing clues to assist in message extraction (Hsu et al, 2013). Roderer et al (2012) pointed out multiple memory strategies as a practical magic to have memory become accurate and rapid after the application. Sonuga-Barke & Fairchild (2012) defined multiple memory strategies as the involved behaviors and thinking in the encoding process when leaners engaging in learning.…”
Section: Multiple Memory Strategiesmentioning
confidence: 99%
“…(2) Learning gains, containing learning satisfaction, achievement, and preference. Roderer et al (2012) indicated that selecting memory strategies suitable for learners could achieve the learning outcomes and reduce time. Sonuga-Barke & Fairchild (2012) revealed that students' use of memory strategies was significantly correlated with the performance of learning achievement.…”
Section: Learning Achievementmentioning
confidence: 99%